Comparative study of routine diagnostic test, C-reactive protein with antithrombin III levels in diagnosis and prognosis of neonatal sepsis - Kacha, Asruti R.; Prasad, Saurabh; Parmar, Panchshila (International Journal of Contemporary Pediatrics, 2018)
Background: Antithrombin III is a potent inhibitor of thrombin mediated vascular injury in the micro-circulation in severe sepsis. This endogenous anti-coagulant is rapidly depleted in the early phases of sepsis as a result of decreased synthesis, increased destruction and enhanced clearance by thrombin-antithrombin complexes. This study was conducted to evaluate the role of antithrombin III level in diagnosis and prognosis of culture proven neonatal sepsis as compared to conventional C-reactive protein. Methods: This prospective study was conducted at a tertiary care hospital in 30 full term, appropriate for gestational age neonates who were admitted in neonatal intensive care unit for suspected sepsis. Results: Out of 30 neonates suspected of sepsis in NICU, 22 turned out to be culture positive. Keeping antithrombin III cut off level ≤150 mg/L, 18 of those 22 culture positive neonates, had antithrombin III level ≤150 mg/L; sensitivity at ≤150mg/L was 81.82%. This was way higher than the 50% sensitivity of CRP, that was found in the study. (Only 11out of 22 culture positive neonates had positive CRP). Conclusions: Antithrombin III level ≤ 150 mg/L is a good indicator for neonatal septicemia and helps to detect neonatal sepsis earlier and more accurately as compared to other conventional laboratory tests like CRP. It also predicts the prognosis of neonatal sepsis more precisely as compared to CRP.